Solve the following system of equations graphically.
x = -5
y = -6
What is the solution set?
{(-6, -5)},
{(-5, -6)},
Ø,

Question

Asked 1/14/2013 8:41:55 AM

Updated 6/9/2014 11:21:13 PM

11 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [6/9/2014 10:53:51 PM]

s

ren15_05|Points 552|

keeneugie|Points 30|

chubang|Points 391|

OxTornado007|Points 6519|

shifa saleheen|Points 9914|

Pinkygrl1183|Points 750|

arkaideman|Points 163|

arrabalon|Points 75|

twistedechoes|Points 46|

barntho5|Points 100|

Question

Asked 1/14/2013 8:41:55 AM

Updated 6/9/2014 11:21:13 PM

11 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [6/9/2014 10:53:51 PM]

Rating

3

y - 4 = 0 rearranging equation the result is: y = 4,

2x - y - 2 = 0

institute y = 4 in the second equation:

2x - 4 - 2 = 0

2x - 6 = 0

2x = 6

x = 3

The solution for the system y - 4 = 0, 2x - y - 2 = 0 is (3, 4)

2x - y - 2 = 0

institute y = 4 in the second equation:

2x - 4 - 2 = 0

2x - 6 = 0

2x = 6

x = 3

The solution for the system y - 4 = 0, 2x - y - 2 = 0 is (3, 4)

Added 6/9/2014 10:53:45 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/9/2014 10:56:23 PM]

3

y = 2x - 3

x + y = 3

institute y in the second equation the result is:

x + (2x - 3) = 3

3x - 3 = 3

3x = 3 + 3 = 6

x = 2

y = 2(2) - 3 = 4 - 3 = 1

The solution for the system y = 2x - 3, x + y = 3 is (2, 1)

x + y = 3

institute y in the second equation the result is:

x + (2x - 3) = 3

3x - 3 = 3

3x = 3 + 3 = 6

x = 2

y = 2(2) - 3 = 4 - 3 = 1

The solution for the system y = 2x - 3, x + y = 3 is (2, 1)

Added 6/9/2014 10:57:41 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/9/2014 11:03:07 PM]

3

(4, 2) is a solution of the system x + y = 6, x = 4.

Added 6/9/2014 10:58:45 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/9/2014 11:03:19 PM]

3

x - y = 4

x + y = 2

adding up the equations the result is:

2x = 6

x = 3

3 - y = 4

-y = 4 - 3 = 1

y = -1

The solution for the system x - y = 4 x + y = 2 is (3, -1) which is the point the lines are intersecting each other if you graph them.

x + y = 2

adding up the equations the result is:

2x = 6

x = 3

3 - y = 4

-y = 4 - 3 = 1

y = -1

The solution for the system x - y = 4 x + y = 2 is (3, -1) which is the point the lines are intersecting each other if you graph them.

Added 6/9/2014 11:02:57 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/9/2014 11:03:35 PM]

3

x + y - 6 = 0

x - y = 0

adding up equations the result is:

2x = 6

x = 3

y = x = 3

The solution for the system x + y - 6 = 0 x - y = 0 is (3, 3)

x - y = 0

adding up equations the result is:

2x = 6

x = 3

y = x = 3

The solution for the system x + y - 6 = 0 x - y = 0 is (3, 3)

Added 6/9/2014 11:05:36 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/9/2014 11:06:13 PM]

3

The best approach for solving this system 5x = y + 6, 2x - 3y = 4 by substitution is: Solve the first equation for y.

Added 6/9/2014 11:08:45 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/9/2014 11:10:10 PM]

3

For the system 2x + y = 6, y = 3x + 4, use the second equation to make a substitution for y in the first equation, the resulting equation is: 2x + (3x + 4) = 6

Added 6/9/2014 11:11:42 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/9/2014 11:17:20 PM]

3

For the following system 3x + y = 1, y + 4 = 5x, use the second equation to make a substitution for y in the first equation, the resulting equation is: 3x + 5x - 4 = 1

Added 6/9/2014 11:13:44 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/9/2014 11:17:31 PM]

3

For the following system x + 5y - 10 = 0, x = 2y - 8, use the second equation to make a substitution for x in the first equation, the resulting equation in simplest form is: 7y - 18 = 0.

x + 5y - 10 = 0,

x = 2y - 8

institute x in the first equation:

2y - 8 + 5y - 10 = 0

7y - 18 = 0

x + 5y - 10 = 0,

x = 2y - 8

institute x in the first equation:

2y - 8 + 5y - 10 = 0

7y - 18 = 0

Added 6/9/2014 11:15:38 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/9/2014 11:17:48 PM]

3

3(y - 3) + 2y = 7 is the resulting equation to use the second equation to make a substitution for x in the first equation for the system 3x + 2y = 7, x - y + 3 = 0.

Added 6/9/2014 11:17:30 PM

This answer has been confirmed as correct and helpful.

3

2(y + 1) + y = 7 is not the result of a substitution in the following system 2x + y = 7, y - x = 1

Added 6/9/2014 11:21:13 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/9/2014 11:23:44 PM]

James's Epistle was probably written from:
Nazareth.
Jerusalem.
Rome.
Bethany.
Capernaum. **Weegy:** James's Epistle was probably written from Jerusalem. (More)

Question

Expert Answered

Updated 5/16/2019 2:27:45 PM

0 Answers/Comments

31,744,609

questions answered

denyang

$659.75

Hearts 13,433 Views 5,736,198 Streams 1,349

sujaysen

$618.50

Hearts 12,565 Views 5,366,409 Streams 1,296

Flora1988

$495.35

Hearts 9,954 Views 5,440,493 Streams 1,288

E L V I E

$491.10

Hearts 9,984 Views 6,205,770 Streams 1,414

PeachyStream97

$458.15

Hearts 9,260 Views 1,724,975 Streams 433

joxce21

$432.45

Hearts 8,945 Views 4,467,611 Streams 1,013

maydj

$419.50

Hearts 8,661 Views 4,480,957 Streams 1,106

Miyaka

$391.10

Hearts 7,979 Views 4,902,071 Streams 1,204

There are no comments.